(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Contribution Of Arabic Coffee Farming to Farmers’ Household Income (Case Study of the Dharma Kriya Farmer Group, Belantih Village, Kintamani District, Bangli Regency). This research aims to analyze the income and contribution of Arabica coffee farming to farmer household income, along identifying the obstacles faced by farmers. The data analysis used in this research is contribution analysis and qualitative descriptive analysis. The type of data used is qualitative and quantitative. The research results show the average income of Arabica coffee farming is IDR 7,221,554/year/respondent with an average cultivated land area of 0.12 Ha. The average income of farmers from farming other than Arabica coffee which comes from oranges and chilies is IDR 41,664,966/year with an average area of cultivated land of 1.01 Ha. Non-farming income in the Dharma Kriya Farmer group an average of IDR 2,430,769/year. The contribution of Arabica coffee farming to the household income of farmers in the Dharma Kriya Farming Group is very low category, abaout 14.07%. Technical obstacles experienced by farmers include pests, diseases and climate. Meanwhile, non-technical obstacles experienced by farmers include the small scale of farming, limited financing and capital, unstable prices, and the use of technology and information which is still relatively low. Suggestions that need to be considered are that farmers in the Dharma Kriya Farming Group should plan the layout of Arabica coffee plants and orange trees well. Farmers also need to follow technological developments that are useful in developing Arabica coffee farming. Apart from that, there needs to be assistance from related agencies, especially agricultural extension workers in the area of the Dharma Kriya Farmer Group so that it remains sustainable.